On-Line Solid Phase Extraction High Performance Liquid Chromatography Method Coupled With Tandem Mass Spectrometry for the Therapeutic Monitoring of Cannabidiol and 7-Hydroxy-cannabidiol in Human Serum and Saliva - Franco, Valentina; Palmisani, Michela; Marchiselli, Roberto; Crema, Francesca; Fattore, Cinzia; De Giorgis, Valentina; Varesio, Costanza; Rota, Paola; Dibari, Vincenza Flora; Perucca, Emilio (Frontiers in Pharmacology, 2022)
Cannabidiol is a novel antiseizure medication approved in Europe and the US for the treatment of seizures associated with Lennox-Gastaut syndrome, Dravet syndrome and tuberous sclerosis complex. We describe in this article a new and simple liquid chromatography-mass spectrometry method (LC-MS/MS) for the determination of cannabidiol and its active metabolite 7-hydroxy-cannabidiol in microvolumes of serum and saliva (50 μL), to be used as a tool for therapeutic drug monitoring (TDM) and pharmacokinetic studies. After on-line solid phase extraction cannabidiol, 7-hydroxy-cannabidiol and the internal standard cannabidiol-d3 are separated on a monolithic C18 column under gradient conditions. Calibration curves are linear within the validated concentration range (10-1000 ng/mL for cannabidiol and 5-500 ng/mL for 7-hydroxy-cannabidiol). The method is accurate (intraday and interday accuracy within 94-112% for cannabidiol, 91-109% for 7-hydroxy-cannabidiol), precise (intraday and interday precision <11.6% for cannabidiol and <11.7% for 7- hydroxy-cannabidiol) and sensitive, with a LOQ of 2.5 ng/mL for cannabidiol and 5 ng/mL for 7-hydroxy-cannabidiol. The stability of the analytes was confirmed under different storage conditions. Extraction recoveries were in the range of 81-129% for cannabidiol and 100-113% for 7-hydroxy-cannabidiol. The applicability of the method to TDM was demonstrated by analysis of human serum and saliva samples obtained from patients with epilepsy treated with cannabidiol.